2011
DOI: 10.1007/s10545-011-9372-y
|View full text |Cite
|
Sign up to set email alerts
|

The adult galactosemic phenotype

Abstract: BackgroundClassic galactosemia is an autosomal recessive disorder due to galactose‐1‐phosphate uridyltransferase (GALT) deficiency. Newborn screening and early treatment do not completely prevent tremor, speech deficits, and diminished IQ in both sexes and premature ovarian insufficiency (POI) in women. Data on how individuals with galactosemia fare as adults will improve our ability to predict disease progression.MethodsThirty‐three adults (mean age = 32.6 ± 11.7 years; range = 18–59) with classic galactosemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
171
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(197 citation statements)
references
References 29 publications
19
171
2
1
Order By: Relevance
“…These problems were similar to those reported previously in individuals with classic galactosemia (Antshel et al 2004;Bosch et al 2004;Ryan et al 2013;Waisbren et al 2012). Parent reports on the SSIS Autism Spectrum subscale indicated that one of five control children and three of seven DG children in the study scored in the "concern" range.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These problems were similar to those reported previously in individuals with classic galactosemia (Antshel et al 2004;Bosch et al 2004;Ryan et al 2013;Waisbren et al 2012). Parent reports on the SSIS Autism Spectrum subscale indicated that one of five control children and three of seven DG children in the study scored in the "concern" range.…”
Section: Discussionsupporting
confidence: 89%
“…Specific symptoms of concern assessed in this section of the SSIS survey included heightened anxiety, social problems, and social withdrawal. As noted above, these same sorts of internalizing behaviors have also been reported for patients with classic galactosemia (Antshel et al 2004;Bosch et al 2004;Ryan et al 2013;Waisbren et al 2012). Children in the DG, no parental concerns group did not exhibit these issues, which is not surprising considering that both the CBCL and SSIS are parent-response surveys, and earlier parent reports were used to stratify the DG children into "parental concern" and "no parental concern" groups.…”
Section: Discussionsupporting
confidence: 56%
“…5 Despite early dietary management, chronic complications such as intellectual deficits, ataxia, speech dyspraxia, premature ovarian insufficiency (POI) and decreased bone mineralization occur in many adults. [10][11][12][13][14][15][16][17][18][19] Different cell and animal models have been utilized to understand the pathogenic mechanisms of the acute neonatal lethality and the long-term complications associated with Classic Galactosemia. Early genetic studies in the yeast Saccharomyces cerevisiae showed that GALT-deficient mutant yeasts are sensitive to galactose in growth medium; but disruption of galactokinase (GALK) function in these yeasts reversed their galactose sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…12 Classic galactosemia (MIM #230400), which affects about 1/47 000 live-births, results from deficient activity of galactose-1-phosphate uridylyltransferase (GALT, EC 2.7.7.12), an ubiquitous key enzyme in galactose metabolism, essential for nursing infants, as lactose represents their primary carbohydrate source. 13,14 The present gold standard of care is a lifelong dietary galactose restriction, which has, however, proven to be insufficient to prevent the long-term sequelae. [13][14][15][16][17] The disorder is caused by mutations in the GALT gene, which profoundly impair GALT enzymatic activity.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The present gold standard of care is a lifelong dietary galactose restriction, which has, however, proven to be insufficient to prevent the long-term sequelae. [13][14][15][16][17] The disorder is caused by mutations in the GALT gene, which profoundly impair GALT enzymatic activity. 15,18,19 GALT is located in chromosome 9p13, arranged into 11 exons spanning about 4.0 kb of genomic sequence, and encodes a 379 amino-acid polypeptide, which is assembled as a B87 kDa homodimer.…”
Section: Introductionmentioning
confidence: 99%